Peranan Metode Isyarat Terhadap Kemampuan Dalam Membaca Al-Qur’an Bagi Penyandang Disabilitas Sensorik Rungu Wicara (PDSRW) Di SLB Dharma Bhakti Dharma Pertiwi - Dinayah, Nidaud; Bunyamin, Mahmudin; Hakiki, Kiki Muhamad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to measure the effectiveness of the application of the sign method in improving the ability to read hijaiyah letters of the Qur'an for Students with Low Speech Sensitivity at SLB Dharma Bhakti Dharma Pertiwi, Bandar Lampung. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews with teachers and parents, and visual documentation during the learning process. The research subjects consisted of 10 deaf students at the SMPLB level in grades VII and IX. The results of the study show that the sign method has a positive impact on improving the ability to read hijaiyah letters. Based on the results of the assessment, three students were in the very good category, four students were in the good category, two students were in the fair category, and one student was in the poor category in reading skills through signs. The improvement can be seen in the consistency of movements, the accuracy of gestures, and the increase in students' motivation and enthusiasm during the learning process. These findings affirm the importance of improving teacher competence in the use of sign methods and the development of more varied and combinative teaching materials to optimize hijaiyah letter learning for deaf students.